Campus and business ecosytem collaboration: A model entrepreneurship education in university - Layoo, Nurhidayah; Raheni, Cahyaning; K. Djawa, Sutrisno; Haluti, Farid (Universitas Jambi, Indonesia, 2025)
This research aimed to find the interaction of entrepreneurship education, family, and outside-the-family environment on the attitudes and entrepreneurial interests of 356 students who have passed the entrepreneurship course. This research is essential because there is a large gap between registered job seekers with undergraduate degrees and those with job placements. The sampling technique used was the quota sampling method. Data were collected through questionnaires and analyzed using the structural equation modeling method. The results showed that entrepreneurship education does not significantly affect attitudes but affects entrepreneurial interest. The family environment influences attitudes and interest in entrepreneurship, and the environment outside the family does not significantly affect interest only if moderated by entrepreneurial attitudes. Indirect influence is more dominant than other variable interactions. The learning model requires collaboration between the campus and the business ecosystem where students interact.